2004
DOI: 10.1016/s0308-597x(03)00083-6
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries co-management—an institutional innovation? Lessons from South East Asia and Southern Africa

Abstract: During the last decade the co-management concept has gained increasing acceptance as a potential way forward to improve fisheries management performance. It has, however, at the same time become increasingly evident that the co-management concept is not clearly defined and means very different things to different people. In this article, we attempt to document experience available from a recent study on fisheries co-management that has researched case studies of various implementations of co-management arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 8 publications
1
91
0
2
Order By: Relevance
“…Domínguez-Torreiro et al (2004), Jentoft (2005), Nielsen et al (2004) and Wilson et al (2003). Similarly to the argument above, it is considered that co-management approaches are essential given the evident failure of top-down approaches (Nielsen and Vedsmand 1999;Wilson 2002).…”
Section: Rights-based Approaches the Way Forwardmentioning
confidence: 99%
“…Domínguez-Torreiro et al (2004), Jentoft (2005), Nielsen et al (2004) and Wilson et al (2003). Similarly to the argument above, it is considered that co-management approaches are essential given the evident failure of top-down approaches (Nielsen and Vedsmand 1999;Wilson 2002).…”
Section: Rights-based Approaches the Way Forwardmentioning
confidence: 99%
“…These are examples in which transaction costs have been very high following the implementation of co-management systems, because in the maritime extractive reserves there is little trust in government initiatives, minimal participatory involvement in the co-management design and projects, and little empowerment. Nielsen et al (2004) observed that one of the main reasons for the lack of success of the modern fisheries management approach was that the topdown approach left fishing communities completely out of the process.…”
Section: Territoriality Institutions and Co-managementmentioning
confidence: 99%
“…Kelleher (1999) and Clifton (2003), and for marine fish stocks, e.g. Jentoft (2003), Nielsen and Vedsmend (1999), Nielsen et al (2004), Pomeroy et al (2001) and Wilson et al (2003). Pomeroy et al (2001) specifically identify the importance of establishing trust and mutual respect amongst partners, of involving fishers in problem recognition and objective setting, of empowering fishers, and of developing incentive structures to induce participation in collective action to manage fisheries.…”
Section: Governance Of Cprs and The Case For Co-managementmentioning
confidence: 99%